Pedagogical and creative perspectives of handwriting, human heritage - Roberto Travaglini (Firenze University Press, 2019)
In this article we are wondering if nowadays more than ever it is possible to consider as well-founded and emerging a pedagogy of the writing gesture, committed to recognise and support the creativity range of a complete educational process closely connected to certain dynamics that subtend the learning of handwriting, considered a common good and a human heritage. The increasingly widespread tendency to remove this educational significance, replacing the handwriting and its implicit complexity by using virtual technological instruments, apparently represents an unstoppable, not devoid of pedagogically relevant consequences.